Towards a Transversal Definition of Psychological Resilience: A Literature Review - Antonella Sisto; Flavia Vicinanza; Laura Leondina Campanozzi; Giovanna Ricci; Daniela Tartaglini; Vittoradolfo Tambone (Medicina, 2019)
Background and objectives: This paper addresses psychological resilience, a multidisciplinary theoretical construct with important practical implications for health sciences. Although many definitions have been proposed in several contexts, an essential understanding of the concept is still lacking up to now. This negatively affects comparisons among research results and makes objective measurement difficult. The aim of this review is to identify shared elements in defining the construct of resilience across the literature examined in order to move toward a conceptual unification of the term. Materials and methods: A literature review was performed using the electronic databases ‘PubMed’ and ‘PsycINFO’. Scientific studies written in English between 2002 and May 2019 were included according to the following key terms: ‘Psychological’, ‘resilience’, and ‘definition’. Results: The review identifies five macro-categories that summarize what has been reported in the recent literature concerning the resilience phenomenon. They serve as a preliminary and necessary step toward a conceptual clarification of the construct. Conclusions: We propose a definition of psychological resilience as the ability to maintain the persistence of one’s orientation towards existential purposes. It constitutes a transversal attitude that can be understood as the ability to overcome the difficulties experienced in the different areas of one’s life with perseverance, as well as good awareness of oneself and one’s own internal coherence by activating a personal growth project. The conceptual clarification proposed will contribute to improving the accuracy of research on this topic by suggesting future paths of investigation aimed at deeply exploring the issues surrounding the promotion of resilience resources.